New Perspectives in the Analysis of Ecdysteroids: A Promising Group of Biologically Active Compounds - Vanyolos, Attila; Bathori, Maria (Current Pharmaceutical Analysis, 2008)
The plant kingdom has remained an inexhaustible reservoir of compounds with a potential of further therapeutic use. Ecdysteroids are such biologically active compounds which were discovered in insects, and later their presence was confirmed in many plant species. They have a tremendous potential in the most modern therapy (gene-switch systems). Ecdysteroids occur in plants together with several other types of natural compounds with similar chromatographic behavior. On the other hand, plants usually contain a series of ecdysteroids with related chemical structures. Sophisticated analytical methods are therefore needed to identify and quantify these compounds in complex biological samples. This paper gives an up-to-date overview on the detection, identification and quantification of ecdysteroids and discusses the advantage and disadvantage of the various methods used in the ecdysteroid analysis. HPLC, TLC and their coupled techniques play an important role in their analysis, with the use of which, the complete resolution of wide structural diversity of ecdysteroids can be attained. This review also offers a well-elaborated, valuable strategy for ecdysteroid screening.
Keywords: Quantification